Motivation as a Determinant of the Personnel Management System in Medical Institutions - Оlena Kravchenko; Bozena Kaminska; Volodymyr Boiko (Health Economics and Management Review)
This study explored the motivational factors of effective management of medical personnel. In this line, the authors highlighted that motivation activates human resources. It is an integral part of the effective management of a medical institution. The main theoretical approaches of foreign and domestic scientists regarding the understanding and interpretation of the personnel management concept were considered. This paper characterized the main employee motivation theories under the procedural, substantive, and behavioral approaches. The authors highlighted the main components of the personnel management system in a medical institution and presented its structure. It was found that motivation is the determinant in the personnel management system. An effectively developed staff motivation system reveals the staff's potential for achieving the organization's goals. Besides, it provides an opportunity to meet the needs of the employee. The obtained results identified the main factors of low motivation of medical staff, which lead to a deterioration in the quality of medical care with all the ensuing consequences. The authors concluded that setting surcharges for employees would interest employees in achieving quantitative and qualitative indicators and strengthening responsibility for providing medical services. The findings showed that the most crucial internal motivation factors provide up to an 80% increase in productivity in the organization. The article presents the components of the motivational mechanism of personnel management in a medical institution. The study findings are of practical importance because they could be used to increase the efficiency of the personnel management system and improve social and labor relations between employees and employers, ensure the achievement of quantitative and qualitative indicators, strengthen responsibility for the quality of medical services. The medical institution will be able to receive more profits, consolidate its position in today's competitive market environment, and create a positive image.